Making Sour Turmeric Herbal Drink to Relieve Dysmenorrhea - K Kurniawan; Nadia Iha Fatihah; Satwika Budi Sawitri (Jurnal Abdimas Kesehatan (JAKes), 2023)
Adolescence is a period of transition or transition from childhood to adulthood which is marked by changes both physically and psychologically, one of the physical changes in adolescents is menstruation. 98.8% of adolescents in Indonesia experience dysmenorrhea during menstruation. Herbal products or phytopharmaceuticals are currently the main alternative for adolescence girls in overcoming dysmenorrhea, one of which is turmeric sour herbal drink. Turmeric sour drink is a drink that is processed with the main ingredient of turmeric. The active compounds of turmeric and sour, namely curcumin and essential oils, have the potential as analgesics that will inhibit uterine contractions, thereby reducing dysmenorrhea. Turmeric is one of the spices that are widely cultivated in Pondok Gontor. Even though they are known for their turmeric production, there are not many adolescence girls in Pondok Gontor Village that produce turmeric and sour herbal drinks. The purpose of this community service is to increase the knowledge and skills of adolescence girls in Pondok Gontor Village in making turmeric and sour herbal drinks. This activity was carried out on 20 adolescence girls in the Hall Pondok Gontor Village in October 2023. The methods used were socialization, demonstration and interactive discussion. Adolescence girls were given training and hands-on demonstrations for processing turmeric. Participants who took part in the activity were very enthusiastic and had many direct discussions related to the manufacturing process. The manufacture of turmeric sour herbal drink can be used as a dysmenorrhea reliever and can be developed into a commercial product and has a selling value.